Patient Sense of Belonging in the Veterans Health Administration: A Qualitative Study of Appointment Attendance and Patient Engagement. Issue 9 (26th September 2022) - Lafferty, Megan; Strange, Wynn; Kaboli, Peter; Tuepker, Anaïs; Teo, Alan R.
Abstract : Background: Health care systems have increasingly focused on patient engagement in efforts to improve patient-centered care. Appointment attendance is an integral component of patient engagement, and missed appointments are an ongoing problem for health care systems. Virtually no studies have examined how the sense of belonging is related to patient engagement within a health care system. Objective: To examine patient experiences in the Veterans Health Administration (VA) with outpatient appointment attendance to identify factors that affect sense of belonging and patient engagement. Research Design and Participants: This study draws from qualitative data collected as part of a study to reduce missed appointments through use of enhanced appointment reminder letters. We conducted semistructured interviews with 27 VA patients with primary care or mental health clinic visits, using deductive and inductive analysis to develop themes. More than half of the participants were Vietnam veterans, 24 were over 40 years old, 21 were White, and 18 were men. Results: We identified 3 factors that influence sense of belonging within the VA: (1) feelings of camaraderie and commitment toward other veterans were relevant to patient experience in the VA; (2) interactions with all staff influenced the engagement a patient felt with a particular clinic, care team, and the VA; (3) personalized communication and messaging could humanize the VA and demonstrate its interest in engaging with veterans. Lastly, we found (4) sense of belonging appeared to promote appointment attendance and patient engagement. Conclusions: There are multiple opportunities to strengthen patients' sense of belonging within the health care system that serves them. For veterans, strategies that build their sense of belonging may be a novel approach to increase appointment attendance and patient engagement in their health care.